2021
DOI: 10.1093/bjsopen/zraa040
|View full text |Cite
|
Sign up to set email alerts
|

Classification of the colonic splenic flexure based on three-dimensional CT analysis

Abstract: Background Mobilization of the splenic flexure can be a challenging surgical step in colorectal surgery. This study aimed to classify the splenic flexure based on the three-dimensional (3D) coordinates of the splenic hilum and left renal hilum. This classification was used to compare splenic flexure mobilization during colorectal resection. Methods CT images of patients with colorectal cancer treated between April 2018 and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The position of the spleen might also have influenced the occurrence of SI. Anatomically, the spleen is fixed retroperitoneally by ligaments, and anatomical changes can make some clinical procedures difficult to perform, allowing complications to occur ( 14 ). In cases where the spleen is located cranially right under the diaphragm, the splenocolic ligament and S/F also tend to be located cranially, and the S/F angle tends to be sharp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The position of the spleen might also have influenced the occurrence of SI. Anatomically, the spleen is fixed retroperitoneally by ligaments, and anatomical changes can make some clinical procedures difficult to perform, allowing complications to occur ( 14 ). In cases where the spleen is located cranially right under the diaphragm, the splenocolic ligament and S/F also tend to be located cranially, and the S/F angle tends to be sharp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since the spleen falls posteriorly away from the S/F in the supine position, insertion of the colonoscope in the supine position might exert opposing traction on the splenocolic ligament and increase the risk of SI ( 5 ). Since body weight is reported to be related to the location of the spleen ( 14 ), evaluating body size as a possible potential risk factor might be valuable in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting the necessity of performing SFM is of importance as, in our cohort, SFM added 29.4 min to the surgical procedure if a colorectal anastomosis was performed. Of note, the wide 95% CI (from 18.7 to 40.1 min) may be explained by the heterogeneity in the anatomy of the splenic flexure, which was shown to modulate the duration of this additional procedure step [ 14 ]. Analysis of 66,068 patients from the NSQIP database found that adding SFM increased operative time from 184 to 220 min (difference of 36 min) [ 13 ], and therefore support our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be bene cial to outline the objective indicators for a di cult SFM and perioperative outcomes of lengthened SFM duration, and its prediction prior to operation may have surgery-related decision-making utility. Currently, a signi cant knowledge gap still exists in this eld as only few studies have focused on this speci c issue (15,16). Our data have revealed that body topographies may be an indicator for di cult SFM, as higher weight, height and BMI values are associated with lengthened SFM durations.…”
Section: Discussionmentioning
confidence: 99%